Alle origini della tutela giuridica del consumatore: fondamenti romanistici della disciplina europea - Ortu, Rosanna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This set to compare certain aspects of weaker contractor’s protections in the contract of sale, which are currently coinciding with those of the consumer, focusing on some instances resent in the Roman law, which deal with contractual disparity. In the Edict of Curuli, the Republican magistrates established special rules for declaring consealed vices in slave and animal sales, assuming an objective liability of the seller who did not abide by the regulations. An important intervention that defined sectoralization of that matter, framed within the sale in general. This resulted in an overlap of planes in legal negotiation framework framework: on he horizontal level, the regulation of the sale was on by the government (ius civile), while on the vertical plane, the local magistrate (ius honorarium, on the basis of the edict was incorporated. This is also the case with the European Directive 1999/44 / EC on the sale of consumer goods, which is the most striking manifestation of the European legislator’s role in consumer protection in contractual matters. As in the ancient world, in Directive 1999/44 / EC regulatory action is justified by the need to create a larger protection area for certain subjects, as well as delimited by content and scope.